A Sub-Region Based Space Vector Modulation Scheme for Dual 2-Level Inverter System - R. Palanisamy; A. Velu; K. Selvakumar; D. Karthikeyan; D. Selvabharathi; S. Vidyasagar (Institute of Advanced Engineering and Science, 2018)
This paper deals the implementation of 3-level output voltage using dual 2-level inverter with control of sub-region based Space Vector Modulation (SR-SVM). Switching loss and voltage stress are the most important issues in multilevel inverters, for keep away from these problems dual inverter system executed. Using this proposed system, the conventional 3-level inverter voltage vectors and switching vectors can be located. In neutral point clamped multilevel inverter, it carries more load current fluctuations due to the DC link capacitors and it requires large capacitors. Based on the sub-region SVM used to control IGBT switches placed in the dual inverter system. The proposed system improves the output voltage with reduced harmonic content with improved dc voltage utilisation. The simulation and hardware results are verified using matlab/simulink and dsPIC microcontroller.